Computer Applications on Pressure Piping Systems and Water Quality Analysis - Ameer, Suhad Abd - Al; Ali, Wissam Abd-; Jasem, Amar (Basrah Journal for Engineering Sciences, 2012)
A part of Basra water network which is near to Bradia water treatment plant is analyzed by using water cad program, water cad is also used for studying the water quality in the model by calculating the age and chlorine concentration for each pipe on the model. This model consist of (21)pipe ,(15)node or junction ,(6)loops, two water pumps one is operated and the second is stand by(each pump has a discharge equal to 0.6 mP3P/sec and a head of 60 m and an electrical control which related with the elevation of water in the tank),one elevated tank &one reservoir of water. The model studied hydraulically for two cases, the first case when the pump is power on and the second case when the pump is power off. Also the direction and discharge for each pipe are calculated. Different results are obtained in two cases. Also the results of water quality studies show that both the age of water and chlorine concentration at any pipe depended on its location with respect to the water treatment plant. Finally the calibration of the model is done in order to check the accuracy of the results.